Laser deposition of Inconel 625/tungsten carbide composite coatings by powder and wire feedstock - Abioye, Taiwo E. (2014)
There is an increasing global demand to extend the life span of down-hole drilling tools in order to improve operation effectiveness and efficiency of oil and gas production. Laser cladding of tungsten carbide/Ni-based alloy metal matrix composite (MMC) coatings is currently being utilised for this purpose. However, the effect of tungsten carbide dissolution on the corrosion performance of the MMC coatings has not been completely understood. In this work, a study was carried out in which laser cladding of a stainless steel substrate using (i) Inconel 625 wire and (ii) tungsten carbide powder (Spherotene)/Inconel 625 wire was undertaken. This work was performed using a fibre laser system and has examined the process characteristics, the microstructure and the corrosion performance of the clad layers. Process characteristics studies were carried out by visual observation of the cladding process within a process window (laser power: 1-1.8 kW, traverse speed: 100-300 mm min-1, wire feed rate: 400-1000 mm min-1, powder feed rate: 25 g min-1). The microstructures were investigated using a combination of optical microscopy, scanning electron microscopy (with energy dispersive X-ray analysis) and X-ray diffraction. The volume fraction of tungsten carbide retained in the composite coatings was determined using image processing software. Corrosion performance was assessed using electrochemical corrosion testing in de-aerated 3.5 wt.% NaCl solution. Well bonded, minimally diluted, pore- and crack-free Inconel 625 wire and Spherotene (WC/W2C) powder/Inconel 625 wire composite coatings were successfully deposited. Cladding process characteristics were categorised into wire dripping, smooth wire deposition and wire stubbing within the range of parameters used in this work. Process maps which predict the characteristic of Inconel 625 wire and Spherotene (WC/W2C)/Inconel 625 wire fibre laser cladding at varying cladding conditions within the process window were developed. The volume fraction of tungsten carbide (WC/W2C) retained in the composite coatings was found to decrease with increasing laser power, traverse speed and wire feed rate. Tungsten carbide dissolution was found to result in the precipitation of intermetallic compounds including M6C and M23C6 in the γ-Ni matrix, which is rich in W and C. The increase in tungsten carbide dissolution was also found to increase the propensity for corrosion in the MMC coatings compared to the Inconel 625 wire coatings. As a result, the corrosion performance of the tungsten carbide/Ni based alloy MMC coatings can be improved by reducing the level of tungsten carbide dissolution through process control.